2010
DOI: 10.1111/j.1463-1326.2009.01189.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral delivery of mouse [d‐Leu‐4]‐OB3, a synthetic peptide amide with leptin‐like activity, in male C57BL/6J wild‐type and ob/ob mice: effects on energy balance, glycaemic control and serum osteocalcin levels

Abstract: Background:We have recently shown that intranasal administration of mouse ]-OB3 reconstituted in Intravail ® to male Swiss Webster mice resulted in significantly higher bioavailability than commonly used injections methods of delivery. The absorption profile associated with intranasal delivery of mouse [D-Leu-4]-OB3 showed an early peak representing absorption across the nasal mucosa, and a later peak suggesting a gastrointestinal site of uptake. Aim and Methods:In the present study, we examined the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 41 publications
(50 reference statements)
3
14
0
Order By: Relevance
“…In this study, we have shown that the biological activity of mouse [D‐Leu‐4]‐OB3 is retained in leptin‐resistant C57BLK/6‐m db/db mice when it is delivered by intranasal instillation in Intravail ® . We recently reported similar results after oral administration of mouse [D‐Leu‐4]‐OB3 in Intravail ® to C57BL/6J leptin‐deficient ob/ob mice [6]. The pharmacokinetics of both intranasal [17] and oral [20] uptake of mouse [D‐Leu‐4]‐OB3 in Intravail ® have been previously described.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…In this study, we have shown that the biological activity of mouse [D‐Leu‐4]‐OB3 is retained in leptin‐resistant C57BLK/6‐m db/db mice when it is delivered by intranasal instillation in Intravail ® . We recently reported similar results after oral administration of mouse [D‐Leu‐4]‐OB3 in Intravail ® to C57BL/6J leptin‐deficient ob/ob mice [6]. The pharmacokinetics of both intranasal [17] and oral [20] uptake of mouse [D‐Leu‐4]‐OB3 in Intravail ® have been previously described.…”
Section: Discussionsupporting
confidence: 62%
“…We and others have shown that ob/ob mice have reduced bone mass, mineralization, bone formation rate and lower serum levels of osteocalciin than their nonobese counterparts of the same age and sex [6,24]. Leptin, given by i.p.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In C57BL/6J ob / ob mice this peptide improved the glucose control and insulin sensitivity [198]. On the basis of peptide [D-Leu-4]-OB-3, the drugs effective in intranasal and oral administration were developed whose activity significantly surpassed that of the same peptide when administered parenterally [199,200]. The peptide analogs of leptin easily penetrated the BBB and specifically interacted with leptin receptors in the CNS, activating leptin signaling in the hypothalamus [185].…”
Section: Leptin Signaling Systemmentioning
confidence: 99%